2007
DOI: 10.1128/jb.01342-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of d -Xylose Metabolism in Caulobacter crescentus by a LacI-Type Repressor

Abstract: In the oligotrophic freshwater bacterium Caulobacter crescentus, D-xylose induces expression of over 50 genes, including the xyl operon, which encodes key enzymes for xylose metabolism. The promoter (P xylX ) controlling expression of the xyl operon is widely used as a tool for inducible heterologous gene expression in C. crescentus. We show here that P xylX and at least one other promoter in the xylose regulon (P xylE ) are controlled by the CC3065 (xylR) gene product, a LacI-type repressor. Electrophoretic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
2
36
0
2
Order By: Relevance
“…Second, although induction of lac expression and dehydrogenase activity is clearly observable in C. crescentus, the level of induction appears modest in comparison to other metabolic systems, both in other bacteria and in C. crescentus, including that used for xylose catabolism (the xyl system) (25,42,53). Poindexter (48) has noted that, for the majority of sugar substrates, the quantitative response of the Caulobacter cell to the sudden availability of a new substrate is not impressive and has suggested that, in dilute environments where a nutrient is likely to be available for only a short time at irregular intervals, dramatic shifts to dedicated pathways may be maladaptive; low-level maintenance of different catabolic systems at all times would be more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although induction of lac expression and dehydrogenase activity is clearly observable in C. crescentus, the level of induction appears modest in comparison to other metabolic systems, both in other bacteria and in C. crescentus, including that used for xylose catabolism (the xyl system) (25,42,53). Poindexter (48) has noted that, for the majority of sugar substrates, the quantitative response of the Caulobacter cell to the sudden availability of a new substrate is not impressive and has suggested that, in dilute environments where a nutrient is likely to be available for only a short time at irregular intervals, dramatic shifts to dedicated pathways may be maladaptive; low-level maintenance of different catabolic systems at all times would be more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Among the latter, the lac promoter of Escherichia coli, as well as its mutant and hybrid forms lacUV5 (6), Ptac (10), and Ptrc (4), have been extensively exploited in combination with its control protein, LacI. In addition, other regulatory elements have been developed and are widely used, including the arabinose promoter of E. coli (19), the xylene (xyl) promoter of Pseudomonas putida (35), and the xylose (xyl) promoter of Caulobacter crescentus (48).…”
mentioning
confidence: 99%
“…For example, transcriptome analysis of C. crescentus metabolizing xylose revealed induction of xylanases and arabinosidases, putative outer and inner-membrane transporters, and a pathway for oxidative metabolism of xylose [11,12]. The xylose regulon is under the control of XylR, a member of the LacI family of bacterial transcription factors [13]. Our results reveal an analogous galacturonate regulon in C. crescentus that is under the control of another LacI family member, HumR.…”
Section: Introductionmentioning
confidence: 67%